The role of drugs and selected dietary factors in cutaneous squamous cell carcinogenesis - Damps, Tatsiana; Czuwara, Joanna; Warszawik-Hendzel, Olga; Misicka, Aleksandra; Rudnicka, Lidia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Cutaneous squamous cell carcinoma represents the second most common non-melanoma skin cancer and its incidence increases worldwide. This review provides an overview of selected exogenous risk factors for cutaneous squamous cell carcinoma, which include drugs (azathioprine, calcineurin inhibitors, hydrochlorothiazide, angiotensin-converting-enzyme inhibitors) and few dietary factors (fat meet, whole milk products, arsenic) to better understand squamous skin cancer etiopathogenesis. Ingredients such as leafy vegetables, nuts, fish, caffeine, niacin are preventive factors for cutaneous squamous cell cancer. The heart transplant recipients have an increased risk of squamous cell carcinoma development than kidney or liver transplant ones and switching photosensitizing azathioprine to mycophenolate mofetil can reduce the incidence of cutaneous squamous cell carcinoma. The great attention should be paid to early change of cardiac photosensitizing antihypertensive drugs to non-photosensitizing ones among patients with a history of prior skin cancers and among organ transplant recipients. Based on current knowledge that ultra-violet radiation is the main risk factor for squamous cell carcinoma development, promotion of the skin self-examination, photoprotection, tanning bed avoidance and early skin cancer diagnosis is important for this tumour prevention.